2022
DOI: 10.1186/s12909-022-03434-3
|View full text |Cite
|
Sign up to set email alerts
|

Remote online global health education among U.S. medical students during COVID-19 and beyond

Abstract: Background Due to the COVID-19 pandemic, the 2021 Harvard Medical School course Clinical Topics in Global Health was offered for the first time as a remote class. We sought to understand student and faculty perceptions of the elective and evaluate the perceived effectiveness of teaching global health using an online education platform. Methods Following the course, students and faculty were invited to complete a combined total of three online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Сложная эпидемиологическая ситуация внесла коррективы в представления студентов медиков о профессионализме врача, особенностях медицинской ра боты и мотивации молодых врачей [Галкин, 2021;Danilina et al, 2020;Keshmiri, Raadabadi, 2022;Sarkis et al, 2020]. Основные принципы и проблемы применения дистанционных методов в медицинском образовании, с которыми столкнулись медицинские вузы, оказались схожими в разных странах [Калиева и др., 2021;Плащевая, Иванчук, 2021;Романова и др., 2022;Сагитова, Ледяев, 2021;Dyrek et al, 2022;Gill, Whitehead, Wondimagegn, 2020;Moschovis et al, 2022]. В качестве негативной тенденции фиксируется, что самоизоляция и последующий период связаны не только с удаленным форматом обучения, но и с дополнительными рабочими нагрузками на студентов медиков, необходимостью расширять профес сиональные компетенции, действовать в ситуации повышенного риска заражения, трансформировать привычное повседневное поведение, что в совокупности часто приводило к снижению мотивации к профессиональной деятельности [Анохин и др., 2022;Холмогорова и др., 2021;Casacchia et al, 2021;Elshami et al, 2021;Golunov, Smirnova, 2021;Zhang et al, 2022].…”
Section: обзор литературыunclassified
See 1 more Smart Citation
“…Сложная эпидемиологическая ситуация внесла коррективы в представления студентов медиков о профессионализме врача, особенностях медицинской ра боты и мотивации молодых врачей [Галкин, 2021;Danilina et al, 2020;Keshmiri, Raadabadi, 2022;Sarkis et al, 2020]. Основные принципы и проблемы применения дистанционных методов в медицинском образовании, с которыми столкнулись медицинские вузы, оказались схожими в разных странах [Калиева и др., 2021;Плащевая, Иванчук, 2021;Романова и др., 2022;Сагитова, Ледяев, 2021;Dyrek et al, 2022;Gill, Whitehead, Wondimagegn, 2020;Moschovis et al, 2022]. В качестве негативной тенденции фиксируется, что самоизоляция и последующий период связаны не только с удаленным форматом обучения, но и с дополнительными рабочими нагрузками на студентов медиков, необходимостью расширять профес сиональные компетенции, действовать в ситуации повышенного риска заражения, трансформировать привычное повседневное поведение, что в совокупности часто приводило к снижению мотивации к профессиональной деятельности [Анохин и др., 2022;Холмогорова и др., 2021;Casacchia et al, 2021;Elshami et al, 2021;Golunov, Smirnova, 2021;Zhang et al, 2022].…”
Section: обзор литературыunclassified
“…При общем положительном отношении к удаленному формату для теоре тических предметов многие студенты сетуют на снижение качества образования во время пандемии. Наибольшая обеспокоенность связана с приобретением практических компетенций и навыков, в том числе при общении с пациентами, что согласуется с результатами подобных исследований в других регионах и странах (на примере Нижнего Новгорода [Романова и др., 2022], Волгограда [Сагитова, Ледяев, 2021], Оренбурга [Чижкова, Нефедова, 2021], Южной Кореи [Kim, Kim, Kim, 2022], Казахстана [Калиева и др., 2021], США [Moschovis et al, 2022] и др. ).…”
Section: медицинское образование и медицина онлайн: отношение студентовunclassified
“…Burgeoning access to the Internet has enabled online instruction to become a reliable, effective, inexpensive, and scalable platform for addressing this need [ 14 , 15 ]. This was demonstrated during the COVID-19 pandemic, which prompted a shift to remote medical educational strategies [ 16 , 17 ]. Internet access and availability have increased globally, particularly in LMICs, making internet access less of a barrier to digital education [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding previous research on online learning platforms, it has been found that: (a) virtual platforms can be used in favor of deep learning [6], (b) online learning can generate significant learning in times of pandemic [7], (c) there is a positive psychological response in favor of the use of the online learning platform [8], (d) virtual platforms are effective for learning a second language such as English [9], ( e) they are successful in the educational process of classical sciences, such as medicine [10,11], (f) virtual platforms increase educational performance, student engagement, evaluation methods, and collaborative learning [12,13]; and (g) the contribution of the metaverse and augmented reality in student satisfaction and interaction in favor of the learning process [14].…”
Section: -Introductionmentioning
confidence: 99%